Selenium Application in Improving Chicory (Cichorium intybus) Productivity and Quality - Umami, N.; Rahayu, E. R. V.; Suhartanto, B.; Agus, A.; Rahman, M. M. (Tropical Animal Science Journal, 2022)
Selenium (Se) is an essential mineral element needed by livestock and human. The amount of Se intake is largely determined by the Se content in the plants (food and feed) consumed. This study aimed to analyze the effect of Se fertilizer on the morphological characters, biomass yield, nutrient content, and in vitro nutrient digestibility of Cichorium intybus. This study was conducted for four months, starting from May to August 2019, located at the Faculty of Animal Science, Universitas Gadjah Mada. The seeds of Cichorium intybus var. Chico was sown in 24 plots and the plots were arranged in a completely randomized block design. Three levels of Se fertilization treatments (0, 3.5, and 7.5 mg/m2) were applied with 8 replicates. Plant defoliation on every 45 days: namely the first defoliation (from sowing to 45 days), the second defoliation (regrowth 1 up to 45 days), and the third defoliation (regrowth 2 up to 45 days). In all studied parameters, the results showed that chicory with Se fertilizer (3.5 and 7.5 mg/m2) was higher (p